Synthesis, characterization, cytotoxic screening, and density functional theory studies of new derivatives of quinazolin-4(3H)-one Schiff bases - Rezvan Rezaee Nasab; Farshid Hassanzadeh; Ghadam Ali Khodarahmi; Mahmoud Mirzaei; Mahboubeh Rostami; Ali Jahanian-Najaf abadi (Wolters Kluwer Medknow Publications, 2017)
A series of novel derivatives of quinazolinone Schiff bases were synthesized from benzoic acid starting material and evaluated for potential cytotoxic activities against the human breast adenocarcinoma (MCF-7) and the human colon adenocarcinoma (HT-29) cell lines. Compared to the reference drug, these compounds showed good cytotoxic activities against studied cell lines especially compounds 4d and 4e. The ground-state geometries of these compounds (4a-g) were optimized at the B3LYP/6-31G* density functional theory (DFT) level. Then maximum absorptions electron affinity, ionization potential, electronegativity (χ), energy gap (Egap), hardness (η), softness (S), electrophilicity (ω), and electrophilicity index (ωi) were calculated and discussed. The quantitative structure-activity relationship (QSAR) properties including the physicochemical parameters were also evaluated and studied. The computed properties of our novel synthesized compounds were compared with erlotinib compound.